Molecular aggregation via partial Gal removal affects physicochemical and macromolecular properties of tamarind kernel polysaccharides. (1st June 2022) - Guo, Rui; Li, Xujiao; Sun, Xianbao; Kou, Yuxing; Zhang, Jun'ai; Li, Deshun; Liu, Yanfang; Zhao, Taolei; Zhang, Hui; Song, Zibo; Wu, Yan
Abstract: The role of molecular aggregation was investigated on physicochemical and macromolecular properties of tamarind kernel polysaccharides via partial degalactosylation (TKPs vs. CTKPs). From the results, their main structural characteristics remained when partially degalactosylated, while primary aggregates as fundamental solution behavior were dynamically converted into higher aggregated forms. Micromorphologically, their conformational changes in different forms of crimping and aggregation could be further promoted by partial Gal removal to assemble on larger scales via hydrophobic interactions. Obviously, the aggregation role was unignorable, especially after partial degalactosylation, which affected TKPs and CTKPs differently concerning viscous behaviors, macromolecular characteristics, amorphous-crystalline transition and thermal stability, probably related to distinctiveness in polymerization degree, chemical structure, conformational entropy, solvent-solute interactions, specific intermolecular associations, etc. Therefore, molecular aggregation in tamarind kernel polysaccharides via specific Gal tailoring could be potential in applicable fields, such as postsurgical adhesion, packaging material design and plasma lipid metabolism. Graphical abstract: Unlabelled Image Highlights: Molecular aggregation enhanced in degalactosylated tamarind kernel polysaccharides. Primary aggregates shifted to higher aggregated forms upon partial degalactosylation. Conformational changes of crimping and aggregation induced by partial Gal removal. Hydrophobic aggregations affecting properties promoted when Gal partially removed. Specific molecular interactions arising from distinctive hydrophobic aggregations.